The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/ccd.26524
|View full text |Cite
|
Sign up to set email alerts
|

Plaque morphology predictors of side branch occlusion after provisional stenting in coronary bifurcation lesion: Results of optical coherence tomography bifurcation study (ORBID)

Abstract: High lipid content of the MV lesion and a contralateral location of lipid in the bifurcation area may contribute to SBOS after provisional stenting. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 45 publications
(55 reference statements)
1
16
0
Order By: Relevance
“…Several angiographic studies have shown that a side branch with severe stenosis was susceptible to occlusion . Previous IVUS and OCT studies have also proven that a thicker plaque at the branch side of the main vessel and side branch ostium would facilitate a plaque shift and side branch occlusion . We also noticed that the DS of the SB before MV stenting was an independent predictor in multivariate analysis rather than DS of SB at baseline.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Several angiographic studies have shown that a side branch with severe stenosis was susceptible to occlusion . Previous IVUS and OCT studies have also proven that a thicker plaque at the branch side of the main vessel and side branch ostium would facilitate a plaque shift and side branch occlusion . We also noticed that the DS of the SB before MV stenting was an independent predictor in multivariate analysis rather than DS of SB at baseline.…”
Section: Discussionsupporting
confidence: 53%
“…In both mechanisms, the disease in the ostial segment of SB would play a more important role than the SB lesion length. Angiographic and IVUS studies also consistently reported that the plaque burden of the SB ostium was a risk factor of SB occlusion . Seo et al also reported that the distal segment of SB was not affected by MV stenting .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies have reported predictors of SB occlusion after MV stenting in coronary bifurcation lesions such as true bifurcation lesion, small SB reference, MV plaque thickness, and preprocedural stenosis of the SB ≥ 50% . However, the reported predictors were concluded from analyses by quantitative coronary angiography, optical coherence tomography (OCT), or intravascular ultrasound rather than directly visual estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Potential reasons might lie in the differences in the bifurcation lesion characteristics between the two cohorts. According to the OCT analysis by Kini et al , bifurcation lesions with SB ostium diameter stenosis >50% were characterized with more frequency of lipid‐rich plaque, more lipid arc, and higher lipid volume index in MV. These characteristics suggested poor fixity of plaque in MV, which led to more likelihood of plaque shift at the bifurcation during MV stenting that compromises the SB ostium and impairs the flow .…”
Section: Discussionmentioning
confidence: 99%